Community and student collaboration to help stunted children in Bojong village Cianjur district - Fahmi Ibrahim; Hasna Raina Salsabila (Universitas Pendidikan Indonesia, 2024)
The pervasive issue of stunting poses a significant threat to the holistic development of children, affecting both their physical and cognitive well-being and, consequently, their prospects. To combat this challenge, a community service group from UPI initiated the Sipenting program (Students Concerned about Stunting). This program, executed in RW 14 of Bojong Village, Cianjur District, adopted diverse strategies, such as home visits and distributing essential groceries to families with stunted children. The primary goal was to enhance awareness regarding stunting and contribute to its reduction in the Cianjur region. The community's active engagement and remarkable enthusiasm were distinctive features of this initiative's impact. Beyond instilling a sense of responsibility, the program fostered collaborative endeavors within the community to tackle the persistent stunting issue, showcasing a positive influence on the collective commitment to addressing this concern. Through these concerted efforts, the initiative has demonstrated tangible progress in raising awareness and mobilizing community resources to combat stunting effectively. Abstrak Masalah stunting yang tersebar luas merupakan ancaman yang signifikan terhadap perkembangan holistik anak-anak, mempengaruhi kesejahteraan fisik dan kognitif mereka dan, akibatnya, prospek masa depan mereka. Untuk mengatasi tantangan tersebut, kelompok pengabdian masyarakat dari UPI menginisiasi program Sipenting (Mahasiswa Peduli Stunting). Program yang dilaksanakan di RW 14 Desa Bojong, Kecamatan Cianjur ini mengadopsi beragam strategi, seperti kunjungan ke rumah dan pembagian sembako kepada keluarga yang memiliki anak stunting. Tujuan utamanya adalah untuk meningkatkan kesadaran mengenai stunting dan berkontribusi terhadap pengurangan stunting di wilayah Cianjur. Keterlibatan aktif masyarakat dan antusiasme yang luar biasa merupakan ciri khas dari dampak inisiatif ini. Selain menanamkan rasa tanggung jawab, program ini juga mendorong upaya kolaboratif dalam masyarakat untuk mengatasi masalah stunting yang terus terjadi, sehingga menunjukkan pengaruh positif pada komitmen kolektif untuk mengatasi masalah ini. Melalui upaya terpadu ini, inisiatif ini telah menunjukkan kemajuan nyata dalam meningkatkan kesadaran dan memobilisasi sumber daya masyarakat untuk memerangi stunting secara efektif. Kata Kunci: KKN; kolaborasi masyarakat; stunting